PENGARUH LINGKUNGAN SEKOLAH TERHADAP PEMBENTUKAN KARAKTER SISWA KELAS X MA BABUSSALAM KALIBENING MOJOAGUNG JOMBANG - Doni Putra Haris; Solihul Anshori (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2024)
This research examines the influence of the school environment on the formation of students' characters. Character education fundamentally involves modifying students' self-development with a clear goal for educational institutions. Schools, generally or broadly defined to include family climate and regional context in character formation, emphasize the development of a strict belief system, unparalleled cultural norms, and a sense of authority, while simultaneously fostering resilience and common personal traits among students. One objective of this study is to describe the character formation of class students. The researcher used a quantitative approach, specifically explanatory and documentation research types. The research findings, examined through calculations of variables X and Y using SPSS in the madrasah environment, indicate that the School Environment correlates with Student Character Formation (since Sig = 0.000, which is < 0.05, hence Ha is accepted). The calculated correlation coefficient (R) of 0.552 > the table value of 0.270 indicates a very strong correlation between peer socialization and learning motivation.